The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1074/jbc.m113.501528
|View full text |Cite
|
Sign up to set email alerts
|

The Strawberry Pathogenesis-related 10 (PR-10) Fra a Proteins Control Flavonoid Biosynthesis by Binding to Metabolic Intermediates

Abstract: Background: Suppression of Fra a gene expression leads to down-regulation of color-producing flavonoid biosynthesis in strawberry.Results: Fra proteins can bind natural flavonoids, which induce conformational changes in conserved loop regions.Conclusion: Fra a proteins control flavonoid biosynthesis through binding to metabolic intermediates.Significance: PR-10 proteins may play a role in the control of secondary metabolism through binding of metabolites to their ligand-binding cavities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
116
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(118 citation statements)
references
References 72 publications
2
116
0
Order By: Relevance
“…Recently, it was shown that Fra a 1.01E is a monomer in solution and in the crystal 3D structure . In this study, the time resolved DNA‐switching measurement system demonstrated dimerization of Fra a 1.01E.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Recently, it was shown that Fra a 1.01E is a monomer in solution and in the crystal 3D structure . In this study, the time resolved DNA‐switching measurement system demonstrated dimerization of Fra a 1.01E.…”
Section: Discussionmentioning
confidence: 50%
“…These results demonstrated that Fra a 1 expression is directly linked to flavonoid biosynthesis and showed that the Fra a 1 allergen has an essential biological function in pigment formation in strawberry fruits . Only recently, the structural analysis of a Fra a 1.03‐catechin complex provided first mechanistic insights into the biological function of Fra a 1 proteins as they may play a role in the control of the flavonoid pathway by binding to metabolic intermediates …”
Section: Introductionmentioning
confidence: 93%
“…The PR10 genes, including those of the tree pollen allergens, are present as a multigene family in various seed plants, and are regulated by highly complex signaling systems (Agarwal and Agarwal 2014). Genetic, structural, and bioinformatic studies have revealed a variety of activities for PR10 proteins, including binding to cytokinins (Pasternak et al 2006;Fernandes et al 2008;Zubini et al 2009) and flavonoids (Casañal et al 2013), membrane permeability (Mogensen et al 2007), and norcoclaurine synthase activity (Lee and Facchini 2010). Furthermore, a Bet v1-superfamily has been defined based on protein structural similarities (Radauer et al 2008), and includes the PR10 family and the PYR1/PYL1/RCAR family of abscisic acid receptors (Ma et al 2009).…”
Section: Introductionmentioning
confidence: 98%
“…The difference in binding activity pointed towards the differences in the binding pockets based on homology modeling. PR-10 proteins have structural and sequence homology with mammalian lipid transport and plant abscisic acid receptor proteins and are predicted to have cavities for ligand binding [61]. A large internal Y-shaped hydrophobic cavity, as determined by three-dimensional structure of PR-10 proteins could be liable for transport of a polar ligands such as fatty acids, flavonoids, cytokinins or brassino steroids in the intracellular spaces [62].…”
Section: Pr-10 Proteins: An Overviewmentioning
confidence: 99%
“…In a recently study, three new members of the PR-10 family, the Fra a proteins, have been identified in strawberry in response to the flavonoid biosynthesis pathway, which is essential for the development of color and flavor in fruits and it was suggested that Fra a proteins could act as transporters or "chemical chaperones" binding to flavonoid intermediates so that they are available to processing enzymes [61]. Furthermore, structural comparisons of the apo forms of Fra a 1E and the Fra a 3-catechin complex indicates that Fra a proteins show significant flexibility in the loop regions surrounding the cavity (loops L3, L5, and L7) and ligandbinding induces important conformational changes suggesting an important role of PR-10 proteins in control of secondary metabolic pathways.…”
Section: Pr-10 Proteins: An Overviewmentioning
confidence: 99%